Aberrant Expression of PAFAH1B3 Affects Proliferation and Apoptosis in Osteosarcoma - Fan, Jian; Yang, Yi; Qian, Ji-kui; Zhang, Xin; Ji, Jia-qing; Zhang, Li; Li, Shan-zhu; Yuan, Feng (Frontiers in Oncology, 2021)
Osteosarcoma is a major malignant tumor of bone and soft tissue, which is presenting with early metastasis and a high mortality rate. Platelet activating factor acetylhydrolase 1B3 (PAFAH1B3), a cancer-relevant molecular, was found to play a vital role in tumorigenesis and aggressiveness in several cancer types. However, the roles and the regulating mechanisms of PAFAH1B3 in osteosarcoma progression remain unclear. PAFAH1B3 expression was detected by immunohistochemistry in 83 osteosarcoma tissues and 44 paired adjacent normal bone tissues. In vitro, loss-of-function assay was performed to explore the role of PAFAH1B3 in osteosarcoma cells. Tumor xenograft growth assay was used to verify the effect of PAFAH1B3 knockdown on osteosarcoma growth in vivo. Chip assay was carried out to investigate the mechanism in osteosarcoma proliferation regulated by PAFAH1B3. PAFAH1B3 was overexpressed in osteosarcoma tissues and cell lines. Moreover, PAFAH1B3 knockdown inhibited osteosarcoma cell proliferation and promoted apoptosis in vitro, and also suppressed osteosarcoma growth in vivo. Furthermore, the proliferative effect of PAFAH1B3 in osteosarcoma was related to the regulation of the expression of EIF4EBP1, MYC, PTGS2 and RPS6KB1. This study demonstrated the biological function of PAFAH1B3 on osteosarcoma proliferation. This research suggested that PAFAH1B3 could be a novel therapeutic target for osteosarcoma patients.